Literary Translation in Periodicals: Methodological challenges for a transnational approach - Stefania Caristia (Benjamins Translation Library, 2020)
While translation history, literary translation, and periodical publications have been extensively analyzed within the fields of Translation Studies, Comparative Literature, and Communication Sciences, the relationship between these three topics remains underexplored. Literary Translation in Periodicals argues that there is a pressing need for an analytical focus on translation in periodicals, a collaborative network of researchers, and a transnational and interdisciplinary approach. The book pursues two goals: (1) to highlight the innovative theoretical and methodological issues intrinsic to analyzing literary translation in periodical publications on a small and large scale, and (2) to contribute to a developing field by providing several case studies on translation in periodicals over a wide range of areas and periods (Europe, Latin America, and Asia in the 19th and 20th centuries) that go beyond the more traditional focus on national and European periodicals and translations. Combining qualitative and quantitative methods of analysis, as well as hermeneutical and sociological approaches, this book reviews conceptual and methodological tools and proposes innovative techniques, such as social network analysis, big data, and large-scale analysis, for tracing the history and evolution of literary translation in periodical publications.